Myelination and isochronicity in neural networks - Kimura, Fumitaka; Itami, Chiaki (Frontiers in Neuroanatomy, 2009)
Our brain contains a multiplicity of neuronal networks. In many of these, information sent from presynaptic neurons travels through a variety of pathways of different distances, yet arrives at the postsynaptic cells at the same time. Such isochronicity is achieved either by changes in the conduction velocity of axons or by lengthening the axonal path to compensate for fast conduction. To regulate the conduction velocity, a change in the extent of myelination has recently been proposed in thalamocortical and other pathways. This is in addition to a change in the axonal diameter, a previously identified, more accepted mechanism. Thus, myelination is not a simple means of insulation or acceleration of impulse conduction, but it is rather an exquisite way of actively regulating the timing of communication among various neuronal connections with different length.